Microanatomical correlates of cognitive ability and decline: normal ageing, MCI, and Alzheimer's disease. - Chance, SA; Clover, L; Cousijn, H; Currah, L; Pettingill, R; Esiri, M (2011)
Few microanatomical measures have been reliably correlated with cognitive measures in aging and Alzheimer's disease (AD), particularly in the early stages of degeneration, such as mild cognitive impairment (MCI). However, cortical minicolumn organization has been shown to correlate with cognitive ability in aging monkeys, and the present study extends this finding to humans. We have previously reported that minicolumn spacing of cells in human association cortex is selectively reduced in normal aging (minicolumn thinning). The present study found that such measures detected early disease changes in MCI as well as further minicolumn thinning and disruption in AD. Plaques, tangles, and minicolumns were quantified, postmortem, for 20 controls, 10 MCI, and 20 AD subjects. Minicolumn changes were correlated with premortem cognitive scores (mini-mental state examination and verbal fluency). Two regions were studied from each brain: association cortex in the planum temporale (BA22) and primary auditory cortex (BA41). The relationship between minicolumns and cognitive function was strongest in association cortex, whereas in primary auditory cortex, it appeared to be an epiphenomenon of overall brain atrophy. Microanatomical changes reflecting selective regional vulnerability to AD pathology and differential involvement in the cognitive deficit of AD are therefore detectable in the early stage of MCI.